Technology and innovation in adult learning - King, Kathleen P. (A Wiley Brand, 2017)
Technology and Innovation in Adult Learning introduces educators and students to the intersection of adult learning and the growing technological revolution. Written by an internationally recognized expert in the field, this book explores the theory, research, and practice driving innovation in both adult learning and learning technology, and illuminates a powerful approach to recognize and leverage these opportunities. Building on current trends and research in technology and its use, each chapter illustrates the need, opportunities, and examples of current and future technologies that scaffold adult learning, and provides comprehensive coverage of both current and emerging challenges.